ECOLOGIA TÉRMICA, PADRÃO DE ATIVIDADE E USO DE HÁBITAT PELO LAGARTO NOTURNO, PHYLLOPEZUS POLLICARIS(PHYLLODACTYLIDAE), EM UMA ÁREA DE CAATINGA NO NORDESTE DO BRASIL - Ferreira, Anthony Santana; Conceição, Breno Moura da; França, Lucas de Melo; Silva, Adilson de Oliveira (Revista Nordestina de Zoologia, 2014)
Understanding the ecological aspects of lizards, such as microhabitat use, thermoregulatory behavior and activity patterns in their microhabitat are important to perceive the complexity of these organisms. This study aimed to analyze the thermal ecology, activity patterns and the microhabitat use of the nocturnal lizard Phyllopezus pollicaris in two dry creek beds in the Unidade de Conservação Estadual Monumento Natural Grota do Angico, Poço Redondo, SE northeastern Brazil. There was a significant positive relationship between body temperature and the environment temperatures, and the temperature of the substrate was the one that explained an additional variation when all environmental variables were put together ( Ts , Ta and 5cm ) . The thermoregulatory behavior found for the species was thermal conformist with the average body temperature of 30.8 ± 2.1ºC and they were more active in the early evening. Regarding microhabitat use, individuals showed a preference for rocks and rock crevices. the vast majority of the individuals were found stuck in the environment what indicates the pattern peeking known for the genus.